Cell cycle of primitive hematopoietic progenitors decelerated in senescent mice is reactively accelerated after 2-Gy whole-body irradiation. Issue 5 (March 2016) - Hirabayashi, Yoko; Tsuboi, Isao; Kuramoto, Kazunao; Kusunoki, Yoichiro; Inoue, Tohru
Aging is considered to be a functional retardation of continuous xenobiotic responses over a lifetime after the developmental period; thus, the effects of ionizing radiation over a lifetime may be somewhat accounted for by a modifier of aging effects. This study was conducted to evaluate the possible/synergic effects of radiation during aging by determining cell-cycle parameters of hematopoietic stem cells/hematopoietic progenitor cells (HSCs/HPCs), such as the percent of cells in cycling, the generation doubling time, and the cumulative cycling-cell fraction, by bromodeoxyuridine-ultraviolet assay, which enables the determination of their cycling capacity in vivo . Colony-forming progenitor cells, such as colony-forming unit (CFU)-granulocyte/macrophage (GM), CFU in the spleen on day 9 (CFU-S9), and CFU-S on day 13 (CFU-S13) for mature, less mature, and immature HPCs, respectively, were evaluated in young and old mice (6 weeks and 21 months of age, respectively) with or without 2-Gy whole-body irradiation and a 4-week recovery period. Then, cell-cycle parameters were evaluated and compared. As a result, the generation doubling time of all types of HPC was prolonged by the irradiation in both young and old mouse groups, except that of CFU-S13 in old mice, which showed acceleration of the cell cycle following the irradiation. In addition, only CFU-S13 in irradiated old mice showed a significant increase in the cumulative cycling-cell-fraction ratio. Significant changes due to the effects of aging and irradiation on HPCs were observed only in the immature HPCs, i.e., the cell cycle of immature HPCs was suppressed by aging without irradiation and was, in contrast, accelerated as the cells recovered from radiation-induced damage. This suggests that the mechanisms of peripheral blood recovery after 2-Gy whole-body irradiation are markedly different between young and old mice, although 21-month-old mice showed almost the same level of recovery as the young mice.